Web-based Library Development Using Codeigniter at SD Muhammadiyah 2 Waru - Ananta, Abdul Mu'iz Yuvan; Nurdyansyah (SAGA: Journal of Technology and Information System, 2024)
Based on (Law of the Republic of Indonesia No. 43 of 2007 concerning Libraries) it is stipulated that libraries are administrative institutions such as written, printed or recorded works that are professional and standardized systems that meet the needs of education, research, information, and preservation, and recreation of visitors (Chapter I Paragraph 1) In the law called "Chapter V Article 14 Paragraph 3" then regulated by all libraries provide good services to advance information and communication technology. Thus the authors try to formulate the problem, namely how to create a computerized school book lending program and use a web-based program using codeigniter at SD Muhammadiyah 2 Waru in order to process data faster and with a minimum error rate.